Growth of Internal Revenue of Baglung Municipality, Gandaki Province, Nepal - Silwal, Sudarshan (Pragnya Sarathi, 2024)
This paper aims to quantify municipalities' internal revenue streams. After the promulgation of Nepal's new constitution in 2015, municipalities include provisions for an independent, three-tiered administration to ensure effective services to the people as well as for a balanced level of economic growth. This study attempts to analyze the growth rate of the internal revenue sources of Baglung Municipality based on the audited financial information of the municipality in the fiscal years from 2018–19 to 2022–23. From the study, a consistent positive growth trend is observed except revenue from other sources. Simply, it can be a positive sign for the local economy. Similarly, of the expenditure, skill development training expenditure for municipal staff has impacted positively for municipal internal revenue generation. This impact is also found statistically significant with strong positive correlation between the variables. Additionally, this study finds that the successful implementation of federalism at local level requires strong leadership, co-ordination among the different levels of government, strong financial plan, diversification of revenue sources, effective and efficient tax collection processes and engagement of local community to gather potential tax revenue sources. Showing the need of creating policies centered on providing effective services to the citizens, this paper will help to make municipals more effective.